Aberrant Expression of High Mobility Group Box Protein 1 in the Idiopathic Inflammatory Myopathies - Day, Jessica; Otto, Sophia; Cash, Kathy; Eldi, Preethi; Hissaria, Pravin; Proudman, Susanna; Limaye, Vidya; Hayball, John D. (Frontiers in Cell and Developmental Biology, 2020)
Introduction High Mobility Group Box Protein 1 (HMGB1) is a DNA-binding protein that exerts inflammatory or pro-repair effects upon translocation from the nucleus. We postulate aberrant HMGB1 expression in immune-mediated necrotising myopathy (IMNM). Methods Herein, we compare HMGB1 expression (serological and sarcoplasmic) in patients with IMNM with that of other myositis subtypes using immunohistochemistry and ELISA. Results IMNM (n = 62) and inclusion body myositis (IBM, n = 14) patients had increased sarcoplasmic HMGB1 compared with other myositis patients (n = 46). Sarcoplasmic HMGB1 expression correlated with muscle weakness and histological myonecrosis, inflammation, regeneration and autophagy. Serum HMGB1 levels were elevated in patients with IMNM, dermatomyositis and polymositis, and those myositis patients with extramuscular inflammatory features. Discussion Aberrant HMGB1 expression occurs in myositis patients and correlates with weakness. A unique expression profile of elevated sarcoplasmic and serum HMGB1 was detected in IMNM.